Uji Daya Hasil Empat Galur Padi Generasi Ke Empat di Lahan Politeknik Negeri Lampung - Lestari, Ana Tri; Kartahadimaja, Jaenudin; Hakim, Nurman Abdul (Jurnal Penelitian Pertanian Terapan, 2017)
The largest food commodity in Indonesia is rice (Oryza sativa), because rice is the main food source for most of Indonesia's population. Rice productivity can be increased, among others through innovation of high yield rice varieties, resistant to biotic and abiotic stress, and have good rice quality. The effort to form high yielding high yielding varieties requires several stages, one of which is power yield test. This research was conducted to obtain potential yield data from the four strains tested in the fourth generation. The strains studied were MS1, MS2, MS3 and ChM strains, with two varieties of varieties, namely Ciherang and Cilamaya varieties. This study used per-line planting method and conducted with Randomize Completly Block Design (RCBD).  Observations were made on selected individual plants as samples. The variables observed were maximum plant height, maximum number of shoots, number of productive shoots, flowering age, harvest age, panicle length, number of grain per panicle, amount of unhulled grain per panicle, total grain per panicle, weight 1,000 grains, Clumps and grain yield per hectare. The data were analyzed by using variance, and if there was any difference between treatments, then the data will be tested further with Least Significant Different (LSD) on stage 5%.. Based on the observation and test, the result of production of each strain is MS1 strain of 7.24 ton.ha-1, MS2 strain of 6.06 ton.ha-1, MS3 strain of 6.29 ton.ha-1, and ChM strain of 6.01 ton.ha-1.